Boardgame Sebagai Media Komunikasi Visual Untuk Mencegah Demensia Sejak Dini Bagi Remaja 15-20 Tahun Di Kota Palembang - Raihan Al-Hafids, Abdul; Mubarat, Husni; Windu Viatra, Aji (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Dementia is a symptom of intellectual function decline characterized by impairment in at least four functions: language, memory, visuospatial abilities (such as measuring distance, distinguishing colors and people), and emotional control. One of the symptoms of dementia is forgetfulness, and most people are still unfamiliar with the term dementia. This lack of awareness is due to insufficient education about dementia. This design project is crucial because it can increase literacy about dementia, enabling preventive measures from a young age by training cognitive skills in adolescents so that their cognitive abilities remain intact into adulthood. The design method used is the Design Thinking method, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. The main media used is a board game which can train players' memory, focus and concentration. Through this design, it is hoped that it will be able to overcome the symptoms of dementia from the teenage years.